Pemberdayaan masyarakat dengan pemanfaatan limbah cakar (cangkang rajungan) sebagai bahan baku pembuatan pakan bandeng - Irma Irma; Kamaliah Kamaliah; Nur Nur; Ratna Ratna; Subariyanto Subariyanto (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Pundatta Baji Sub-district, Labakkang Sub-District, Pangkep Regency, there is an industrial processing of crab meat for export. In the production process, in addition to crab meat, the crab crabs also produce shells or crab shells. if it is not managed properly it can cause environmental pollution. Utilization of crab shells as one of the ingredients for fish feed rations. the waste has a protein content. Utilization of crab shell waste is a solution in repeating and one of the efforts to reduce the volume of waste that continues to increase in Pundatta Baji Sub-District, Labakkang District, Pangkep Regency. The purpose of the implementation of the Program is to increase the knowledge, skills and economy of the community by utilizing crab shell waste into fish food and the diversification of milkfish products. Implementation methods namely Lecture, Question and Answer Method, Demonstration Method, Monitoring and Evaluation. Activities 1. The implementation of the PKM-M Program can increase public knowledge about the benefits of recycled crab shell waste as fish feed in Pundatta Baji Village. 2. Feed making training improves community skills in applying technology to process crab shell shell waste into high-value milkfish feed. 3. Improving the economy of the community of Pundatta Baji Pangkep Sub-district in processing milkfish products for product diversification (milkfish). The results of PKM-M activities with feed training and product diversification supported by the community in Pundatta Baji Village were proven by respondents of 20 people indicating 65% were in the very high category.